2022
DOI: 10.1021/acsami.2c01658
|View full text |Cite
|
Sign up to set email alerts
|

Solid Polymer Electrolytes Based on Gellan Gum and Ionic Liquid for Sustainable Electrochromic Devices

Abstract: Materials sustainability is becoming increasingly relevant in every developed technology and, consequently, environmentally friendly solid polymer electrolytes (SPEs) based on gellan gum and different quantities of ionic liquid (IL) 1-ethyl-3-methyl-imidazolium-thiocyanate [Emim]­[SCN] have been prepared and applied in electrochromic devices (ECDs). The addition of the IL does not affect the crystalline phase of gellan gum, and the samples show a compact morphology, surface uniformity, no phase separation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
(119 reference statements)
0
16
0
Order By: Relevance
“…These polymers include poly(lactic acid) [45,46] and polyurethanes due to their high degree of tuneability in mechanical properties and conductivity as highlighted in recent Reviews and articles [13,47–50] . In this context, polymers based on vegetable oils with long fatty acids, [51–53] cellulose, [54] gums, [55] and others similar bio‐derivatives [56,57] are of high interest as potential ion conductors owing to their ether and carbonyl functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers include poly(lactic acid) [45,46] and polyurethanes due to their high degree of tuneability in mechanical properties and conductivity as highlighted in recent Reviews and articles [13,47–50] . In this context, polymers based on vegetable oils with long fatty acids, [51–53] cellulose, [54] gums, [55] and others similar bio‐derivatives [56,57] are of high interest as potential ion conductors owing to their ether and carbonyl functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] In addition, related studies have shown that gel electrolytes also promote the improvement of electrochromic properties. [23][24][25][26] Hydrogels in gel electrolytes promise brand new applications in exible electronic elds such as stretchable ECDs, 27 ionic skin, [28][29][30][31] so robotics, 32,33 personal healthcare monitoring, 34 drug delivery, 35 articial organs, 36 and wearable electronics [37][38][39] due to their inherent excellent exibility, high optical transparency, high ionic conductivity, and good biocompatibility. PVA hydrogels have been widely studied due to their nontoxicity, biocompatibility, degradability, water retention, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic Liquids (ILs) are ideal electrolytes due to their high electrical conductivity, negligible vapor pressure, non-flammability, wide electrochemical window, and excellent thermal stability. 52 Previous studies found that the addition of ILs enhanced the conductivity of various polymers, such as gellan gum, 25 poly(3,4-ethylenedioxythiophene):poly(styrene-sulfonate)/PVA, 53 and poly(vinylidene fluoride- co -hexafluoropropylene). 54 However, the reports of IL-modified PVA-borax dynamically cross-linked polymer matrixes and the mechanism of enhancing their electrical conductivity in previous studies are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids (ILs) have been fascinating the scientific community for decades due to their rich spectrum of physical and chemical properties, , which enable a wide range of practical applications from catalysis to electrochemistry. They serve as ideal platforms for realizing the green transformation and development of the chemical industry, particularly for the electrocatalytic conversion of CO 2 , in which ILs act as cocatalysts with metal electrodes to reduce the redox potential of CO 2 . , Actually, not only in CO 2 conversion but also in many other chemical reactions, supported IL catalysts (SILCA) and supported catalysts with ILs layer (SCILL) are widely used, where the ILs work by loading on the solid surface and undergo electron transfer with the reactants . Therefore, the interface plays an essential and ubiquitous role in the catalytic process. , It is well-known that contact electrification is a universal electron transfer phenomenon that can occur between any contact materials, , and hence there must be electron transfer between ILs and solid surfaces, which may largely affect the performance of ILs.…”
mentioning
confidence: 99%